Woman and math. Education for Gender Equity and Human Rights - Riveros Santa, Francy Angélica (Instituto para la Investigación Educativa y el Desarrollo Pedagógico, IDEP, 2017)
This article presents an innovative experience, in relation to the education in gender equity, as pedagogic scene in the class of mathematics. For that reason, through the scientific study of the mathematical contributions, life testimonies have been discovered where, in all cases, sexist, cultural and social barriers have been identified for women that stand out in the mathematics field. Consequently, a project was developed seeking to motivate and empower the students by working on reflections, discussions, socializations, where orientation aspects such as human rights have emerged.